2017
DOI: 10.1007/s10096-017-3095-4
|View full text |Cite
|
Sign up to set email alerts
|

MRSA prevalence rates detected in a tertiary care hospital in Austria and successful treatment of MRSA positive patients applying a decontamination regime with octenidine

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) decontamination regimens predominantly use chlorhexidine bathing in combination with mupirocin nasal ointment. However, resistances in Staphylococcus aureus strains are increasingly common and there is a need of alternative, safe and feasible protocols. This interventional cohort study performed at the Albert Schweitzer Hospital in Graz, Austria, aimed to (1) determine MRSA prevalence at different body sites and (2) assess the efficacy of the decontamination u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…In addition, it is the only antiseptic which remains active locally for up to 48 hours and is not associated with systemic side effects [26, 27]. OCT is widely used in Europe for skin, mucous membrane, and wound antisepsis [25, 28] as well as for patient decolonization in various clinical settings [2931], and resistances have not been reported [32]. Even though very few cases of irritant and/or allergic contact dermatitis have been reported when superficial skin infections were treated with OCT [33, 34], it is generally considered to be a safe and efficient antiseptic [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is the only antiseptic which remains active locally for up to 48 hours and is not associated with systemic side effects [26, 27]. OCT is widely used in Europe for skin, mucous membrane, and wound antisepsis [25, 28] as well as for patient decolonization in various clinical settings [2931], and resistances have not been reported [32]. Even though very few cases of irritant and/or allergic contact dermatitis have been reported when superficial skin infections were treated with OCT [33, 34], it is generally considered to be a safe and efficient antiseptic [25].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Reiser et al (2017) suggested that Octenidine body wash did not reduce the rate of SSI for patients undergoing coronary artery bypass grafts, but did significantly decrease the harvest site and organ/space sternal SSIs. For MRSA colonisations, Pichler et al (2018) concluded that application of Octenidine body wash reduced MRSA colonisations by 93%, although this study was undertaken on medical rather than surgical wards. Similarly Chow et al (2018) found that Octenidine body wash reduced MRSA prevalence rates by 58% in an extended care facility.…”
Section: Discussionmentioning
confidence: 97%
“…Rekomendowany jest do stosowania na powierzchnię skóry, błon śluzowych i ran [1]. Działanie przeciwbakteryjne przejawia w stosunku do bakterii Gram-ujemnych i Gram-dodatnich, w tym bakterii atypowych oraz gronkowca złocistego opornego na metycylinę (methicillin-resistant Staphylococcus aureus -MRSA) [1][2][3][4]. Wykazano także, że preparat inaktywuje wirusy otoczkowe, których przedstawicielami są m.in.…”
Section: Wprowadzenieunclassified
“…It is recommended to be applied on skin, mucous membranes and wounds [1]. Antibacterial activity of this antiseptic encompasses Gram-positive and Gram-negative bacteria, including atypical bacteria and methicillin-resistant Staphylococcus aureus (MRSA) [1][2][3][4]. Moreover, it has been proved that Octenisept ® inactivates enveloped viruses, that are represented inter alia by herpes simplex virus and hepatitis B virus [5] and has protozoicidal properties against Trichomonas vaginalis [6].…”
mentioning
confidence: 99%